Design of Semi Automatic Announcement System In The Public Address System Part of The Main Branch Office Soekarno-Hatta International Airport Angkasa Pura II, Inc - Putra Maulana Yusuf; Irwan Iftadi; Agus Ramelan (Universitas Sebelas Maret (UNS), 2022)
Facilities and services are needed reliable for the comfort of airplane passengers. One of the important facilities in airport services is the Public Address System (PAS). PAS is a notification system using sound electronically distributed with amplifiers, loudspeakers, and microphones. PAS functions to provide information from the airport and airlines to be conveyed widely to airplane passengers. In order to reduce the possibility of misinformation or delivery of unclear information from the operator, the author aims to create Semi Automatic Announcement System (AAS) website where someone no longer needs to speak directly but only needs to enter a notification sentence, then the system from the website will speak or also can be referred to as text to speech. The system is expected to reduce misinformation so that information can be clearly understood by passengers.